(untitled) (Research, Society and Development, 2020)
The present study aimed to analyze the prevalence of high-density lipoprotein (HDL-c) cholesterol dyslipidemia and associated factors in the quilombola population in Bahia. This is a population-based study, with 850 adults of both sexes. HDL-c dyslipidemia was determined to be <50 mg/dl for women and <40 mg/dl for men, as updated by the Brazilian Dyslipidemia and Atherosclerosis Prevention Directive. Poisson regression, crude and adjusted, was used to test associations. The prevalence of HDL-c dyslipidemia was 17.5% (95% confidence interval: 14.9: 20.0). The factors associated (p<0.05) with dyslipidemia were: age, marital status, hypertension and diabetes. It is concluded that HDL-c dyslipidemia is more prevalent in older, married, hypertensive and diabetic quilombolas.